1981
DOI: 10.1021/ma50004a021
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 nuclear magnetic resonance chemical shifts and the microstructures of the fluoropolymers poly(vinylidene fluoride), poly(fluoromethylene), poly(vinyl fluoride), and poly(trifluoroethylene)

Abstract: Simultaneous 'H and '9 broad-band decoupled l3C NMR spectra are recorded for poly(vinylidene fluoride) (PVFJ, poly(fluoromethy1ene) (PFM), poly(viny1 fluoride) (PVF), and poly(trifluoroethy1ene) (PF&). Observed 13C chemical shifts are compared to those calculated as a function of stereoregularity and/or defect structure, i.e., head-to-head to tail-to-tail (H-H:T-T) addition of monomers. Calculated chemical shifts are obtained through enumeration of the numbers and kinds of y effects (three-bond gauche arrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…14 This can be ascribed to the smaller content of regio-irregular structure in PVDF (5%, from solid-state 19 F NMR data 8 ) compared with that of PVF (10.6%, from solution-state 13 C NMR data 22 ). As clarified in Fig.…”
Section: H 1r Measurementsmentioning
confidence: 99%
“…14 This can be ascribed to the smaller content of regio-irregular structure in PVDF (5%, from solid-state 19 F NMR data 8 ) compared with that of PVF (10.6%, from solution-state 13 C NMR data 22 ). As clarified in Fig.…”
Section: H 1r Measurementsmentioning
confidence: 99%
“…Perfluoroalkyl iodides or a,v-diiodoperfluoroalkanes act as efficient chain transfer agents (CTA), since they easily undergo CF 2 -I bond cleavage [5,6,9,11,12,14,15,[20][21][22] leading to low molecular weight molecules. Most studies on the direction of addition of the telogen onto the asymmetric monomer (VDF) have shown that the addition mainly occurs onto the methylene groups of VDF [11,15,[20][21][22][23][24][25][26][27], and that it is regioselective. The stepwise telomerizations of VDF and HFP with perfluoroalkyl iodides or a,v-diiodoperfluoroalkanes acting as CTAs have been investigated [15,21,28].…”
Section: Introductionmentioning
confidence: 99%
“…11 In a previous paper using 13 C and RIS modelling, which they afterwards deemed erroneous, the same authors had evaluated the fraction of HH-TT defects as 50%. 12 An update, based on 19 F{ 1 H} NMR spectra, estimated the HH-TT additions to be 20% of the overall additions. 13 More recently, using the definition of reverse additions given by Cais (HH-TT additions sequence), and more modern NMR techniques (higher frequency and more efficient 1 H decoupling), Harris reached an estimation of around 13.5%.…”
Section: A Introductionmentioning
confidence: 99%
“…Figure12. WAXS patterns and intensity profiles of slow-cooled (sc) and fast-cooled (fc) PTrFE (Entry 12, Table1) and PTrFE-XA (Entry 5, Table1).…”
mentioning
confidence: 99%